Identification of sources of resistance to leafhopper (Amrasca biguttula biguttula) in sunflower: Identification of sources of resistance to leafhopper (Amrasca biguttula biguttula) in sunflower - P S SRINIVAS; H P MEENA; M Y DUDHE (Journal of Oilseeds Research, 2023)
Among the 135 sunflower lines evaluated during summer, 2020-22, ten lines were confirmed resistant to leafhopper. Leafhopper (Amrasca biguttula biguttula) is a major sucking pest that occur mostly in rabi/summer season and cause yield loss of up to 40% in India. Chemical control effects pollinators. Host plant resistance is an ecologically and economically promising alternative pest management tool. Presently, none of the available hybrids are leafhopper resistant. Leafhopper resistant cultivars significantly reduces plant protection cost. Stable sources of resistance are needed to be identified to develop resistant cultivars.